FAKTOR SOSIAL-EKONOMI YANG MEMPENGARUHI PETANI MENGADOPSI INOVASI PENGELOLAAN TANAMAN TERPADU JAGUNG DI GORONTALO - Sumarno, Jaka; Hiola, Fatmah Sari Indah (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
Integrated Crop Management (ICM) of maize has been disseminated since long time in all production centers in Indonesia, including Gorontalo. However, the application at the farmer level has not been optimal so that it has not yet expanded. This study aims to measure theÂ adoption rate of the components of maize ICM technology, and to identify socio-economic factors that affect the application of maize by farmers in Gorontalo District. The study was conducted on lowland dryland agro ecosystem in Tibawa Subdistrict and highland dryland agro ecosystem in Bongomeme Subdistrict, Gorontalo District. Site selection was done purposively with the consideration that the districtÂ and sub-district were maize production centers, and had implemented various programs to increase maize production with the application of ICM from various government agencies. The survey was carried out in February-May 2015. The adoption rate of maize ICM component by respondents farmers used the weighting (score). Socio-economic factor analysis methods that influence the application of maize ICM using logistic regression model. The results showed that the accessibility of farmers to the supporting sources of farming such as capital (credit), market, and technology sources significantly affected the adoption of ICM technology. Steps that can be taken to improve farmers access to credit in formal financial institutions (banks) include providing flexible credit scheme, easy, not procedural, and not burdensome. Increased access of farmers to the source of technology can be done through increased frequency of extension, the implementation of technology dissemination that reaches more farmer groups and farmers.